Staphylococcal enterotoxins fail to disrupt membrane integrity or synthetic functions of Henle 407 intestinal cells. - Buxser, S (1981)
The potential cytotoxic activity of purified staphylococcal enterotoxins for mammalian cells was evaluated. The effects of staphylococcal enterotoxins A (SEA) and B (SEB) on cell membrane integrity as measured by leakage of labeled cytoplasmic constituents ([3H]uridine), amino acid transport (lysine and aminoisobutyric acid), and macromolecular synthesis (protein, ribonucleic acid, and deoxyribonucleic acid) was evaluated for a human intestinal epithelial cell (Henle 407). No evidence of cytotoxicity by any of these criteria could be detected for cell monolayers incubated with SEA for periods of between 30 min and 24 h. Purified staphylococcal hemolysins (alpha- and delta-toxins) were shown to exert cytotoxicity by the leakage and amino acid uptake assays. In efforts to detect synergistic effects between enterotoxin and the staphylococcal cytotoxins, membrane functions were evaluated after sequential or combined treatment with enterotoxin and alpha-toxin or with enterotoxin and delta-toxin. In no instance could a contribution to cytotoxicity by the staphylococcal enterotoxin be detected. That the assays were sufficiently sensitive to detect synergistic effects was shown by the greater than additive effects achieved with a combination of alpha- and delta-toxins. The data, contrary to previous reports, showed that staphylococcal enterotoxins did not behave as bacterial cytotoxins.